Synthesis and Applications of Encapsulated Glycol-Stabilized Lyotropic Cholesteric Liquid Crystal Hydrogels - Yan-Ting Lin; Chung-Yu Kuo; Yi Shen; Alexander V. Emelyanenko; Chun-Yen Liu (Gels)
The micro-phase segregation of two incompatible components on a nanometer scale results in a unique solvent-induced extended anisotropic arrangement. With the addition of a chiral dopant, lyotropic liquid crystals can be induced to adopt a helical structure, forming lyotropic cholesteric liquid crystals capable of reflecting incident light. In this study, to prevent fluid leakage in lyotropic materials, we encapsulated a series of hydrogel-stabilized lyotropic liquid crystals, presenting tunable structural colors visible in all directions, mimicking the color-changing characteristics of living organisms. Hydrogel scaffolds with controllable swelling behaviors were engineered by incorporating crosslinking monomers. To ensure stable integration of lyotropic liquid crystals, high-boiling-point ethylene glycol was employed as a fluid during the fabrication process. This study extensively explores the relationship between tensile force, temperature, and pressure and the color changes in lyotropic liquid crystals (LC). The results indicate that lyotropic LC membranes, stabilized by ethylene glycol and PDMS encapsulation, exhibit long-term stability, rendering them suitable for applications in temperature and pressure sensing. This approach ensures the continuous presence and stability of lyotropic liquid crystals within the hydrogel matrix.